Illocutionary Acts in a Letter to Europe from a Palestinian - Jufrisani, Nadia Davina; Mardiah, Zaqiatul (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
Open letter is a letter directed for a person which generally can be read by many people. One of the example of open letter is A Letter to Europe from a Palestinian which is written by Majed Abusalama and this letter was published on 18 October 2023 by Al Jazeera. The open letter contained sentences that came from Abusalama views and experiences that are related to Palestine. Therefore, the resercher decided to used A Letter to European from a Palestinian as an object research to find out the illocutionary acts in the open letter. The method used in this research is qualitative descriptive in order to explore and explain the research data desciptively. The result showed that the open letter had four types of illocutionary acts which include 7 representatives, 7 directives, 9 expressives and 1 commissives. First, the function of representative is for stating. Second, directive had variety of functions such as requesting, advising and inviting. Third, expressive represented the meaning of disappointment, griefing and deploring. Fourth, commissive had a function of promising.